Análise dos portais da transparência dos municípios do Estado do Ceará como instrumento de disclosure da gestão pública - Oliveira, Adolfo Dantas (2018)
Faced with the obligation of public bodies to maintain a portal capable of reporting to citizens and other interested parties on public spending, this research intends to verify to what extent the Transparency Portals of the Municipalities of the State of Ceará comply with the minimum requirements, those required by the Law of Access to Information, through the creation of a respective index, as an instrument of social control of public management, based on the Brazilian legislation combined with the identification of the elements available in the Portals as to the Information Content, Usability and the Availability of information, and verifying which population indicators, social and economic of the municipalities influence the levels of disclosure of the Portals. It is an exploratory study with a quantitative approach, carried out through the application of an existing evaluation model. The research identified that the Transparency Portals studied still have a lot to be developed in the criterion of informations transparency, information content, usability and availability of information, for effective support to social control, and that the selected indicators do not have the power to influence the transparency of the municipalities of Ceará.